Pengaruh Fasilitas Pasien BPJS Terdahap Kepuasan Pelanggan Pada Rumah Sakit Tingkat II Udayana Denpasar - Trihendratmoko, Oke (CITIZEN CHARTER, 2017)
Improvement of facilities is one effort to provide customer satisfaction. Customer satisfaction is one of the factors of good service quality. The purpose of this study was to determine the effect of facilities used BPJS patients on customer satisfaction at the Hospital Level II Udayana Denpasar. The research method used is associative method of quantitative approach with the intention to find the influence between facility (variable X) to customer satisfaction (variable Y). Primary data in this study was obtained through the distribution of questionnaires as much as the number of samples that is 61 people BPJS patients at the Hospital Level II udayana. The result of analysis of this research findings shows that partial influence of BPJS (X) facility on customer satisfaction (Y) at Udayana Denpasar Level II Hospital is positive and significant. This is based on the results of linear regression analysis that obtained a positive beta value of 0.852. To test whether or not significant, tested by using t-test analysis that obtained t-count = 12,164 and t-table = 1.999 which means t-count> t - table with a significance value of 0.000 <0.05. This means Ho is rejected and Hi accepted. So it can be concluded that the partial influence of the facilities BPJS (X) on customer satisfaction (Y) at Udayana Hospital Level II Denpasar is positively significant. Of 71.5%. This is based on the results of linear regression analysis which obtained R square value of 0.715 which means that 71.5% variation of customer satisfaction from patient of BPJS user at Udayana Level II Hospital influenced by available BPJS facility, while the rest equal to 32,9% Explained by other factors not included in the model. Keywords: Facilities, Customer Satisfaction, BPJS